The influence of work factors on reproductive health of female workers in Sidoarjo industrial area, Indonesia - Tri Martiana; Rahman, Firman Suryadi; Putri Mahdang; Hamedon, Titi Rahmawati; Jalaludin, Juliana (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Female workers have different abilities and physiology to male workers. Thus, female workers are very sensitive to some hazards in workplace environment. The existing hazards in work environment can cause various effects towards pregnancy among female workers. The objective of this study was to analyze the influence of work factors including shift work, work attitude, and work duration on reproductive health. Methods: The study was a cross-sectional study. The number of research sample was 109 female workers selected by simple random sampling. The respondents were female workers in plastic and soft drink industry in Sidoarjo. Primary data was collected by using questionnaires. The dependent variable was the reproductive health of female workers. Reproductive health status of female workers includes menstrual disorders and pregnancy disorders. The independent variables included work pattern, work duration, and shift work. Results: The percentage of respondents who were married was 81.7%. The percentage of respondents experiencing reproductive disorders was 63.3% in which 60.6% cases were menstrual disorders and 20.2% cases were pregnancy disorders. The results of logistic regression test showed that reproductive health during pregnancy was affected by shift work (p=0.007). Conclusion: Female workers who worked in the evening and at night shift had high risks of pregnancy disorders and miscarriage than female workers who worked at normal working hours. Working in shifts and the irregular working hours also associated with the miscarriage occurence. Companies need to provide protection for pregnant workers in order to avoid irregular shift work and evening or night shift.